PEMBERIAN BEBERAPA KONSENTRASI BIO-URIN SAPI PADA BIBIT TANAMAN GAHARU (Aquilaria malaccensis) - Kurnia Dwi Putri; Sampoerno ' '; Fifi ' Puspita (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This research was aimed to  know influence of concentrate Bio-urine of cow and to get the effective concentrate of Bio-urine of cow. The research was conducted at the greenhouse of Faculty of Agriculture University of  Riau  from Mei 2015 to July 2015.This research is an experimental with 5 treatments (no concentrate,30% concentrate, 40% concentrate, 50% concentrate, and 60% concentrate) with 4 replications and each  replications consist of 2 plants. Data obtained from this study were analyzed by ANOVA and continued with Duncan’s New Multiple Range Test at 5%. The results showed thatgiven of some concentrate Bio-urine of cow influencing gaharu on all parameters. And given of 60% concentrate is the most effective concentrate for Seed agarwood grow up.   Key words: Seed agarwood, Bio-urine of cow.